THE HUMAN RELATIONS THEORY AS A STRATEGY FOR PEOPLE MANAGEMENT (CIPEEX, 2025)
This study analyzes the application of the principles of the Human Relations Theory in people management, exploring how these fundamentals can improve motivation, well-being, and employee performance in organizational environments. The research includes a bibliographic review and a survey of studies in companies that promote humanized leadership and communication practices, with qualitative data collected through interviews and questionnaires. From the data, the relevance of transformational and transactional leadership styles to foster learning behaviors is evidenced, as well as the impact of friendships and financial decisions that prioritize interpersonal relationships on organizational culture. The results demonstrate that an integrated approach, considering leadership, motivation, and well-being policies, strengthens productivity, cohesion, and talent retention, promoting a healthy and sustainable work environment.
Keywords: Human Relations Theory; Organizational well-being; Humanized work environment; Interpersonal relationships; Productivity.